“La disgrafía en el proceso de enseñanza-aprendizaje” - Estrella Hidalgo, Rosa Mercedes (2023)
Education is one of the strengths that the human being has to function in society, therefore, it must meet all the educational needs present in it, because there are students with some type of learning difficulty, especially in writing, as is the digraph. However, few are the teachers who manage to diagnose the type of insufficiency that appears in the school classrooms. Thus, the objective of the research is to characterize dysgraphia in the teaching and learning process for the improvement of the academic performance of the students of the sixth grade of EGB of the School of Basic General Education ´´Latacunga", parish Once de Noviembre, Latacunga canton, Cotopaxi province, school year 2022-2023. The methodology used is based on qualitative research focused on the interpretive paradigm, which aims to describe, analyze and interpret reality. Faced with this, it has been necessary to apply the inductive method, accompanied by documentary or bibliographic and field research, even from the particular to the general. Finally, the instruments were applied with the interview technique, with which they allowed the collection of relevant information for the analysis and formulation of research results. The results obtained allowed us to determine that dysgraphia problems affect student learning, because they have difficulties when carrying out activities that involve writing, which makes it impossible for the child to understand or read what they write, thus affecting their learning pace.